Detection of Defects in Diamond by Etch‐Pit Formation. Issue 21 (17th July 2019) - Shimaoka, Takehiro; Ichikawa, Kimiyoshi; Koizumi, Satoshi; Watanabe, Kenji; Teraji, Tokuyuki
Abstract : Correlation between the reverse current density J R of diamond vertical Schottky barrier diodes (SBD) and the shape of the etch pits is investigated. Etch pits form throughout the whole epitaxial layer area with a density of 6.8 × 10 4 –3.0 × 10 5 cm −2 . Most etch pits are isolated‐type, with flat‐bottom or point‐bottom shape. A typical pit size is 3–5 μm in width and 1–3 μm in depth. Some etch pits aggregate linearly with a size of >10 μm. The SBDs show large J R when these etch pit clusters appear. The etch pit cluster density is <10 3 cm −2 . Abstract : This study shows detection of defects that induce large reverse current density J R of diamond Schottky barrier diodes (SBDs). Correlation between J R of vertical SBDs and shape of the etch pits is investigated. The SBDs show large J R when etch pit clusters appear through plasma etching.